Caracterização de Padrões de Formas de Fundo da Foz do Rio São Francisco - VITAL, HELENICE; DE OLIVEIRA, ARNO MASCHMANN; TABOSA, WERNER FARKATT (Pesquisas em Geociências, 2001)
On the basis of a regional side-scan sonar survey covering a distance of 12 km on the São Francisco River Mouth between Piaçabuçu and Cabeço-Pontal da Barra (NE Brazil) a variety of bedforms have been distinguished. The river bed morphology of this area can be characterized by three main patterns: dunes, ripples and planar beds. Sand dunes occur as extensive 2D and 3D dune fields. Between Piaçabuçu and Fitinha Island the dunes are asymmetric indicating a sand movement toward the river mouth. These dunes range in height from 1 to 2 m, and in wavelength from 30 to 90 m. Between Fitinha Island and Negra Island large asymmetric dunes with smaller symmetric ones superimposed can be seen, showing tidal influence. At the river mouth, the dunes give place to symmetrical ripples with height smaller than 0,3 m and wavelength shorter than 1 m. The dune and ripples fields can be intercalated by planar beds.